Las luchas de bandos nobiliarios como factor determinante del conflicto comunero en Plasencia (1520-1522) - Diago Hernando, Máximo (Cuadernos de Historia Moderna, 2006)
The revolt of the “Comunidades” evolved in a different way in each of the Castilian towns that took part in the rebellion. In this article the author gives account of the peculiarities of this political movement in Plasencia, the city of Extremadura that supported the cause of the Comunidades with more determination. Nevertheless, he proves that in this city the movement of the Comunidades meant almost nothing else but an aggravation of the conflict that for a long time had been opposing two noble factions, named Carvajales and Zúñigas, in which the local oligarchy was then divided. This fact contributes to understand the reason why the conflict in Plasencia continued for several months after the “comunero” army had been defeated in Villalar (April 1521), and that the monarchy didn´t impose any punishment on the local leaders that supported the cause of the Comunidades.